Aid Flows to the Water Sector : Overview and Recommendations - Winpenny, James; Trémolet, Sophie; Cardone, Rachel; Kolker, Joel; Kingdom, Bill; Mountsford, Lyndsay (World Bank, Washington, DC, 2016)
This report provides data and insights on the role of grant funding and concessional financing in meeting the Sustainable Development Goal for water (SDG 6, known as the water SDG). These sources of funding are collectively referred to in this report as aid flows to the water sector. This report was prepared as an input into the High-Level Panel on Water. Data analysis was conducted using two main databases on aid to the water sector. The Organisation for Economic Cooperation and Development Assistance Committee (OECD/ DAC) database is the most comprehensive, while the WASHfunders.org database provides complementary data on aid from philanthropic organizations. These databases were complemented by an inventory of the main institutions providing aid to the water sector, as well as interviews with selected providers of aid to the water sector, including leading multilateral development banks (MDBs), bilateral donor agencies, and international nongovernmental organizations (NGOs). This analysis provides the basis for recommendations on how to improve the aid architecture to the water sector and mobilize financing to achieve the water SDG.